The words you are searching are inside this book. To get more targeted content, please make full-text search by clicking here.

tablaintegrales

Related Publications

Discover the best professional documents and content resources in AnyFlip Document Base.

tablaintegrales

tablaintegrales

Anexo D

Tabla de Integrales

(PUEDE SUMARSE UNA CONSTANTE ARBITRARIA A CADA INTEGRAL)

1. xn dx = 1 xn+1 (n = −1)
n+1

2. 1 dx = log |x |
x

3. ex dx = ex

4. ax dx = ax
log a

5. sen x dx = − cos x

6. cos x dx = sen x

7. tan x dx = − log |cos x|

8. cot x dx = log |sen x|

9. sec x dx = log |sec x + tan x| = log tan 1 x+ 1 π
2 4

227

228 Tabla de Integrales

10. csc x dx = log |csc x − cot x| = log tan 1 x
2

11. arcsen x dx = x arcsen x + √ − x2 (a > 0)
a a a2

12. arccos x dx = x arccos x √ − x2 (a > 0)
a a − a2

13. arctan x dx = x arctan x − a log a2 + x2 (a > 0)
a a 2

14. sen2 mx dx = 1 (mx − sen mx cos mx)
2m

15. cos2 mx dx = 1 (mx + sen mx cos mx)
2m

16. sec2x dx = tan x

17. csc2x dx = −cot x

18. senn x dx = − senn−1 x cos x + n − 1 senn−2 x dx
n n

19. cosn x dx = cosn−1 x sen x + n − 1 cosn−2 x dx
n n

20. tannx dx = tann−1x − tann−2x dx (n = 1)
n−1

21. cotnx dx = cotn−1x − cotn−2x dx (n = 1)
n−1

22. secn x dx = tan x secn−2 x + n − 2 secn−2 x dx (n = 1)
n−1 n − 1

23. cscnx dx = cot x csc n−1x + n − 2 cscn−2x dx (n = 1)
n−2 n − 1

24. senh x dx = cosh x

25. cosh x dx = senh x

229

26. tanh x dx = log |cosh x|

27. coth x dx = log |sen hx|

28. sech x dx = arctan (senh x)

29. csch x dx = log tanh x = − 1 log cosh x + 1
2 2 cosh x − 1

30. senh2x dx = 1 senh 2x − 1 x
4 2

31. cosh2x dx = 1 senh 2x + 1 x
4 2

32. sech2x dx = tanh x

33. senh−1 x dx = xsenh−1 x √ (a > 0)
a a − x2 − a2

34. cosh−1 x dx = xcosh−1 x − √ − a2 cosh−1 x > 0, a > 0
a xcosh−1 a + √x2 − a2 a
x cosh−1 x < 0, a > 0
a x2 a

35. tanh−1 x dx = xtanh−1 x + a log a2 − x2
a a 2

36. √ 1 dx = log √ = sen h−1 x (a > 0)
a2 + x2 x + a2 + x2 a

37. 1 dx = 1 arctan x (a > 0)
a2 + x2 2 a

38. √ − x2 dx = x √ − x2 + a2 arcsen x (a > 0)
a2 2 a2 2 a

39. a2 − x2 3 dx = x 5a2 − 2x2 √ − x2 + 3a4 arcsen x (a > 0)
2 8 a2 8 a

40. √1 dx = arcsen x (a > 0)
a2 − x2 a

41. 1 dx = 1 log a+x
a2 − x2 2a a−x

230 Tabla de Integrales

42. 1 dx = √x
a2 a2 − x2
(a2 − x2) 3
2

43. √ dx = x √ ± a2 ± a2 log √
x2 ± a2 2 x2 2 x + x2 ± a2

44. √ 1 dx = log √ = cosh−1 x (a > 0)
x2 − a2 x + x2 − a2 a

45. 1 dx = 1 log x
x(a + bx) a a + bx

46. √ + bx dx = 2 (3bx − 2a) (a + bx) 3
xa 15b2 2

47. √ bx dx = √ + bx + a √ 1 dx
a+ 2a x a + bx
x

√x 2 (bx − 2a) √ a + bx
a + bx 3b2
48. dx =

49. √1  √1a log √√aa++bbxx−+√√aa (a > 0)
x a + bx  (a > 0)
dx =  √2−a arctan a+bx
−a

50. √ √ √
a2 − x2 dx = a2 − x2 − a log a + a2 − x2
x
x

51. √ − x2 dx = − 1 a2 − x2 3
x a2 3 2

52. √ − x2 dx = x 2x2 − a2 √ − x2 + a4 arcsen x (a > 0)
x2 a2 8 a2 8 a

√1 1 a+ √ a2 − x2
x a2 − x2 a x
53. dx = − log

54. √x √
a2 − x2 dx = − a2 − x2

55. √ x2 dx = − x √ − x2 + a2 arcsen x (a > 0)
a2 − x2 2 a2 2 a

56. √ √ √
x2 + a2 dx = x2 + a2 − a log a + x2 + a2
x
x

231

57. √ dx √ arccos | a | √ x (a > 0)
x2 − a2 = x2 − a2 − a x = x2 − a2 − arcsec a
x

58. √ ± a2 dx = 1 x2 ± a2 3
x x2 3 2

59. √1 dx = 1 log √x
x x2 + a2 a a + x2 + a2

60. √1 dx = 1 arccos | a | (a > 0)
x x2 − a2 a x

√ 1 dx = ± √ x2 ± a2
x2 x2 ± a2 a2x
61.

62. √x √
x2 ± a2 dx = x2 ± a2

1 √1 log 2ax+b−√b2−4ac (b2 > 4ac)
63. + bx + c dx = b2−4ac 2ax+b+ b2−4ac (b2 < 4ac)
ax2 √2 √2ax+b
4ac−b2 arctan 4ac−b2

64. x dx = 1 log ax2 + bx + c − b ax2 1 dx
ax2 + bx + c 2a 2a + bx + c

65. √1 dx = √1a log |2ax + b + 2√a√ax2 + bx + c| (a > 0)
√1 √−2ax−b
ax2 + bx + c −a arcsen b2−4ac (a < 0)

66. √ + bx + c dx = 2ax + b √ + bx + c + 4ac − b2 √1 dx
ax2 4a ax2 8a
ax2 + b + c

√x √ ax2 + bx + c b √1
a 2a
67. ax2 + bx + c dx = − ax2 + bx + c dx

68. √1 dx = −√1c log 2√c√ax2+bx+c+bx+2c (c > 0)
x (c < 0)

x ax2 + bx + c √1 arcsen √bx+2c
−c |x| b2−4ac

69. √ 1 x2 − 2 a2 (a2 + x2)3
x3 x2 + a2 dx = 5 15

70. √ dx = ∓ (x2 ± a2)3
x2 ± a2 3a2x3
x4

71. sen ax sen bx dx = sen(a − b)x − sen(a + b)x a2 = b2
2(a − b) 2(a + b)

232 Tabla de Integrales

72. sen ax cos bx dx = cos(a − b)x − cos(a + b)x a2 = b2
2(a − b) 2(a + b)

73. cos ax cos bx dx = sen(a − b)x − sen(a + b)x a2 = b2
2(a − b) 2(a + b)

74. sec x tan x dx = sec x

75. csc x cot x dx = −csc x

cosm x senn x dx = cosm−1 x senn−1 +x + m − 1 cosm−2 x senn x dx =
m+n m + n cosm x senn−2 x dx
76. senn−1 x cosm+1 x n−1
m+n m+n
= − +

77. xn sen ax dx = − 1 xn cos ax + n xn−1 cos ax dx
a a

78. xn cos ax dx = 1 xn sen ax − n xn−1 sen ax dx
a a

79. xneax dx = xneax − n xn−1eax dx
a a

80. xn log(ax) dx = xn+1 log ax − (n 1 1)2
n+1 +

81. xn (log ax)m dx = xn+1 (log ax)m − n m 1 xn (log ax)m−1 dx
n+1 +

82. eax sen bx dx = eax (a sen bx − b cos bx)
a2 + b2

83. eax cos bx dx = eax (b sen bx + a cos bx)
a2 + b2

84. sech x tanh x dx = −sech x

85. csch x coth x dx = −csch x